2018
DOI: 10.1073/pnas.1809050115
|View full text |Cite
|
Sign up to set email alerts
|

Adult spinal motoneurons change their neurotransmitter phenotype to control locomotion

Abstract: SignificanceAn intriguing feature of the nervous system is its plasticity—the remarkable lifelong capacity to change and adapt in light of intrinsic and extrinsic stimuli. Among the many different adaptive mechanisms that occur within the nervous system, changes in neurotransmission form an important plasticity-bestowing mechanism in the reconfiguration of neuronal circuits. Here, we reveal that physical activity and spinal cord injury can switch the neurotransmitter phenotype of the fast axial motoneurons to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 45 publications
(71 reference statements)
1
51
1
Order By: Relevance
“…In adult zebrafish and rats, there is no evidence for cholinergic descending projections from the brain to the spinal cord but only intraspinal cholinergic innervation [34][35][36] . However, to test for the possibility of transient cholinergic neurons from the brain that project to the nAChR-expressing interneurons in the spinal cord, we also examined the expression of cholinergic genes in the brain.…”
Section: Pre-and Postsynaptic Cholinergic Genes Are Expressed In the mentioning
confidence: 99%
“…In adult zebrafish and rats, there is no evidence for cholinergic descending projections from the brain to the spinal cord but only intraspinal cholinergic innervation [34][35][36] . However, to test for the possibility of transient cholinergic neurons from the brain that project to the nAChR-expressing interneurons in the spinal cord, we also examined the expression of cholinergic genes in the brain.…”
Section: Pre-and Postsynaptic Cholinergic Genes Are Expressed In the mentioning
confidence: 99%
“…However, it must be noted that these latter studies were cross-sectional and the tested populations were elite in terms of their performance, making it difficult to separate the effect of training and heritability (Georgiades et al 2017). In conclusion, because many different plasticity mechanisms co-exist in the spinal cord (Wang & Brehm, 2017;Bertuzzi et al 2018;Chen et al 2019), short-and long-term general and task-specific adaptations most probably co-exist.…”
Section: Discussionmentioning
confidence: 99%
“…A change in phenotype in the RVM is supported by prior literature which showed that neutral cells adopted both ON-cell and OFF-cell phenotypes after inflammation resulting in increases in both ON-cells and OFF-cells [43]. Exercise can alter neuron phenotype as evidenced by a prior study showing fast, but not slow or intermediate, motor neurons increase expression of glutamate after exercise training [2].…”
Section: Discussionmentioning
confidence: 53%